2005
DOI: 10.1007/s11075-005-9005-3
|View full text |Cite
|
Sign up to set email alerts
|

Computing ECT-B-splines recursively

Abstract: ECT-spline curves for sequences of multiple knots are generated from different local ECT-systems via connection matrices. Under appropriate assumptions there is a basis of the space of ECT-splines consisting of functions having minimal compact supports, normalized to form a nonnegative partition of unity. The basic functions can be defined by generalized divided differences [24]. This definition reduces to the classical one in case of a Schoenberg space. Under suitable assumptions it leads to a recursive metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 24 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…The relations between the coefficients α of two consecutive intervals have already been obtained in (41), (42), and (43). With the notations introduced in (30) and (51) they can be summarised as follows:…”
Section: The B-spline Basismentioning
confidence: 99%
See 2 more Smart Citations
“…The relations between the coefficients α of two consecutive intervals have already been obtained in (41), (42), and (43). With the notations introduced in (30) and (51) they can be summarised as follows:…”
Section: The B-spline Basismentioning
confidence: 99%
“…Our overview will be as brief as possible. For further acquaintance with Extended Chebyshev spaces, see, for instance, [45,43,31,32,28,34], with Chebyshevian splines, see [45,43,5,8], with piecewise Chebyshevian splines, see [4,29,28,40,41,33,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Via de Boor-Fix type dual functionals, he proved that the total positivity of all such connection matrices (i.e., all their minors are nonnegative), was sufficient to ensure existence of a B-spline basis and of a de Boor-type evaluation algorithm. Later on, under the same total positivity assumption, a further proof of the existence of a B-spline basis was given by Mühlbach via generalised Chebyshevian divided differences [4,27,28]. In the meantime we had shown that, in any such spline space, existence of blossoms was equivalent to existence of a B-spline basis in the space itself and in all spline spaces deduced from it by knot insertion [18].…”
mentioning
confidence: 93%
“…This very general framework has been considered by several authors (see, for instance [4,18,20,[26][27][28]), among whom the very first was Barry [1]. In his approach, the section-spaces were defined by means of given weight functions and associated differential operators, as is classical for Extended Chebyshev spaces.…”
mentioning
confidence: 99%